Disclosure of Related Party Transactions and Information Regarding Transfer Pricing By the Companies Listed On Bucharest Stock Exchange - Liliana Feleagă; Ioana Neacşu (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Related party transactions and transfer prices have begun to be considered a powerful instrument of financial frauds as a result of the recent financial scandals. Transactions with related parties situated in tax havens are one of the principal elements which contribute to the faltering confidence of the investors. We focused on the related party transactions and transfer prices in the context of Romanian listed companies given the features of the local institutional context. For example, 36% of the companies listed on Bucharest Stock Exchange have affiliates in tax havens. The objective of this study is to analyse how the Romanian companies listed on Bucharest Stock Exchange disclosed during 2012-2014 the related party transactions and information regarding transfer pricing and what institutional factors are associated with disclosure. We found that companies audited by a Big Four, large companies and companies which perform transactions with non-resident related parties disclose more information compared with companies audited by a non-Big Four entity, small or medium companies and companies which perform transactions with resident related parties. We also found that factors like sector of activity and nature of capital (foreign or local) do not significantly influence the disclosure of related party transactions and transfer pricing aspects. Results might be of interest for other emerging economies, offering insights with regards to the importance of such disclosures for investors. On the other hand, the results might be useful for developed countries (e.g. western investors) which find Romania an attractive country in terms of investments.
Keywords: M41; 650; related party transactions; transfer pricing; financial reporting; investors; performance